Psychological health in COVID-19 patients after discharge from an intensive care unit - Carola, Valeria; Vincenzo, Cristina; Morale, Chiara; Pelli, Massimiliano; Rocco, Monica; Nicolais, Giampaolo (Frontiers in Public Health, 2022)
Along with physical changes, psychological changes are detectable in patients with COVID-19. In these patients, the stressful experience of intensive care unit (ICU) hospitalization may aggravate psychological conditions. Our study examines the short- and long-term psychological consequences of COVID-19 in ICU patients. COVID-19 patients completed the self-rating questionnaires Kessler 10 Psychological Distress Scale (K10), Perceived Stress Scale-10 (PSS), Impact of Event Scale Revised (IES-R), and Post-traumatic Growth Inventory (PTGI) and were clinically interviewed 1 and 6 months after discharge. Altered behavioral-psychological symptoms and patients' strategies (adaptive vs. maladaptive) for coping with stress during and after hospitalization were coded during clinical interviews. Between 20 and 30% of patients showed moderate symptoms of depression or anxiety and perceived stress 1 and 6 months after discharge. Sleep problems, difficulty concentrating, confusion in placing events, and fear of reinfection were observed in many (6–17%) patients. At 6 months, only 7% of patients showed PTSD symptoms, and 50% showed post-traumatic growth in the “appreciation of life” sub-scale. Finally, 32% of subjects were classified as “maladaptive coping patients,” and 68% as “adaptive coping patients.” Patients who adopted “adaptive” coping strategies showed significantly lower levels of anxious-depressive symptoms and perceived stress when compared to subjects with “maladaptive” strategies at both time points. Coping strategy had no effect on PTSD symptoms or post-traumatic growth at 6 months. These findings clarify the short- and long-term psychological effects of intensive care due to COVID-19 infection and demonstrate that patient characteristics, particularly strategies for coping with stress, seem to play a critical role in psychological outcomes.